Comparative gene expression study highlights molecular similarities between triple negative breast cancer tumours and feline mammary carcinomas. (14th January 2022) - Sommerville, Lara; Howard, Jane; Evans, Shane; Kelly, Pamela; McCann, Amanda
Abstract: Triple negative breast cancer (TNBC) is a rare, highly metastatic subtype of breast cancer that typically develops tumours of a high histological grade. As TNBC is negative for the oestrogen, progesterone and HER2 receptors it is also not eligible for targeted hormonal therapies. Therefore, those diagnosed with TNBC are faced with a very poor prognosis. Feline mammary carcinomas (FMCs) have been shown to share key characteristics of TNBC and are being investigated as novel animal models of this disease. A study by Granados‐Soler et al., investigating prognostic markers of FMCs provided the basis of this research, and their prognostic value in TNBC was evaluated using a ' data‐mining ' research approach. Overall, the comparative genomic aspect of this research identified several potential prognostic markers translatable across TNBC and FMCs. These prognostic markers warrant further investigation in comparative oncology studies.